2011
DOI: 10.2151/jmsj.2011-403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solar Radiation Amount and Synoptic-scale Wind on the Local Wind "Karakkaze" over the Kanto Plain in Japan

Abstract: A climatological and numerical study of "Karakkaze," a type of local wind in Japan, was conducted. First, winter days under a winter-type synoptic pressure pattern with daily minimum relative humidity of less than 40% were classified according to strong wind (wind speed � 9 ms −1 , Karakkaze day), medium wind (6 ms −1 � wind speed < 9 ms −1 ), and weak wind (wind speed < 6 ms −1 ). Secondly, the spatial patterns of the surface wind in each category are confirmed by the Japan Meteorological Agency (JMA)-Automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
2
11
1
Order By: Relevance
“…1b) from 2000 to 2016. The present study specifically defined the formation of Karakkaze based on the following four criteria derived from previous studies (e.g., Yoshino 1975;Kusaka et al 2011): (1) wind speed at a height of 10 m at Maebashi must be more than 8 m s −1 , (2) the most frequent wind direction at 10 m at Maebashi must be between 270° and 360° while a strong wind is blowing, (3) relative humidity at 2 m at Maebashi must be < 40% when the most strong wind blows on the event, and (4) there must be no precipitation at Maebashi while the strong wind is blowing. We defined a Karakkaze event as a period that satisfied the above criteria and during which the wind speed was 4 m s −1 or more.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1b) from 2000 to 2016. The present study specifically defined the formation of Karakkaze based on the following four criteria derived from previous studies (e.g., Yoshino 1975;Kusaka et al 2011): (1) wind speed at a height of 10 m at Maebashi must be more than 8 m s −1 , (2) the most frequent wind direction at 10 m at Maebashi must be between 270° and 360° while a strong wind is blowing, (3) relative humidity at 2 m at Maebashi must be < 40% when the most strong wind blows on the event, and (4) there must be no precipitation at Maebashi while the strong wind is blowing. We defined a Karakkaze event as a period that satisfied the above criteria and during which the wind speed was 4 m s −1 or more.…”
Section: Methodsmentioning
confidence: 99%
“…The islands are thus in an environment that favors the development of strong winds caused by terrain, and many local winds occur in Japan (Yoshino 1975;Kusaka and Fudeyasu 2017). Well-known examples of such local winds include the Karakkaze (Yoshino 1975(Yoshino , 1978Kusaka et al 2011), Matsubori-kaze (Yoshino 1975;Kurose et al 2002), Hirodo-kaze (Yoshino 1975;Fudeyasu et al 2008), Yamaji-kaze (Saito and Ikawa 1991;Saito 1993), and Kiyokawadashi (Yoshino 1975;Ishii et al 2007;Sasaki et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6b). The mechanical effect of strong winds, which occasionally breaks the surface inversion layer, is an additional factor in night-time high-temperature events (White 2009;Kusaka et al 2011). In the case of January 13, 2000, however, the wind speed was not strong at Saroma (Fig.…”
Section: Januarymentioning
confidence: 99%
“…Kondo (1983) called these increased daytime wind speeds thermal convective winds. Kusaka et al (2011) also reported that strong local surface winds on the Kanto Plain during winter, so-called Karakkaze, have a clear diurnal variation and show a strong correlation with the upper-level wind speed but a weak correlation with the daily sunshine duration. The wind speed near the top of the PBL is relatively weak in the daytime, but it is strengthened at night because the development of a stable atmosphere decouples low-level winds, and general winds flow over the PBL (Blackadar 1957).…”
Section: Introductionmentioning
confidence: 97%